A study of invertebrate drift in Smith Valley Creek, Wisconsin - Mueller, Keith A. (My University, 1981)
The invertebrate drift and benthic invertebrate fauna in Smith Valley Creek (LaCrosse County, Wisconsin) were studied from October 14, 1976 to May 14, 1977 and the influences of physical and chemical variables were examined.
Keywords: Smith Valley Creek.; Wisconsin.; Freshwater invertebrates.